Synonymy of the genus Delmohius Brennan and Goff, 1978 with Carebareia Goff and Brennan, 1977 (Trombidiformes: Trombiculidae) - Bassini-Silva, Ricardo (2020)
Chiggers have been studied throughout the world for their role in disease transmission. Venezuela has the largest chigger diversity in South America. In a review of Venezuelan genera, two monotypic genera described from Robinson's Mouse Opossum collected in Falcon State and after examination of the types of both genera, it was found that Delmohius hardyi Brennan and Goff and Carebareia johnstoni Goff and Brennan are the same species. Therefore, we are proposing the synonymy of Delmohius with Carebareia.